Methods for studying nucleic acid/drug interactions - Wanunu, Meni.; Tor, Yitzhak (Boca Raton : Taylor & Francis, 2012)
"Since most therapeutic efforts have been predominantly focused on pharmaceuticals that target proteins, there is an unmet need to develop drugs that intercept cellular pathways that critically involve nucleic acids. Progress in the discovery of nucleic acid binding drugs naturally relies on the availability of analytical methods that assess the efficacy and nature of interactions between nucleic acids and their putative ligands. This progress can benefit tremendously from new methods that probe nucleic acid/ligand interactions both rapidly and quantitatively. A variety of novel methods for these studies have emerged in recent years, and Methods for Studying DNA/Drug Interactions highlights new and non-conventional methods for exploring nucleic acid/ligand interactions. Designed to present drug-developing companies with a survey of possible future techniques, the book compares their drawbacks and advantages with respect to commonly used tools. Perhaps more importantly, this book was written to inspire young scientists to continue to advance these methods into fruition, especially in light of current capabilities for assay miniaturization and enhanced sensitivity using microfluidics and nanomaterials"--Provided by publisher.
section 1. Classical techniques -- section 2. Emerging techniques.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: DNA-drug interactions -- Research; Electronic books